Factors Determining The Capital Structure of Banking Companies Listed On The Indonesian Stock Exchange - Muliyani, Muliyani; Marisa, Marisa (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
This study aims to determine the effect of Return on Asset (ROA), Sales Growth, Liquidity and Company Size on the capital structure of the banking industry listed on the Indonesia Stock Exchange in 2019-2023. This study uses secunter data with panel data regression as an analysis tool and data processing assistance with Eviews. The results of hypothesis testing show that ROA has no significant effect on capital structure, that companies that use relatively small debt have a high rate of return on investment. Sales growth does not have a significant effect on the mode structure, where companies that have a high potential sales growth rate will tend to generate greater cash flow so that the company will ultimately rely more on internal funding. Liquidity has a significant effect on the capital structure, where if the greater the liquidity, the greater the capital structure and if the smaller the liquidity, the smaller the capital structure. The size of the company does not have a significant effect on the capital structure, this can be interpreted that the size of a company does not affect the capital structure of the Company. The results of this study are also expected to be a reference for future research to increase the number of research variables and increase the number of research populations in various sectors and increase the research period.